Kaposi′s Sarcoma In A Young Female : Some Unusual Observations - Sharma Ashok Kumar; Jajoo Suhas (Wolters Kluwer Medknow Publications, 1997)
A patient of Kaposiâ€s sarcoma which followed a progressive course but without systemic involvement or signs of acquired immunodeficiency is reported. Some unusual features in clinical presentation were noted.